The Implementation of Counseling Learning Method to Improve Arabic Speaking Skills for the Freshmen - Ida Miftakhul Jannah; Mohamad Thohir (Arabic Education Program IAIN Pekalongan, 2020)
A method in teaching Arabic as a second language is an important tool to meet learning goals and deliver the subject. This study aims to describe the implementation of the Counseling Learning Method (CLM) in Arabic teaching for new students in a university. It investigates the implementation of CLM to improve Arabic speaking skills and the obstacles in it. A qualitative approach is used in this research through observation, interview, and documentation during the Arabic teaching on “Kalam li al Mubtadiin” subject. The Participants of this research are twenty-one first-year students and a lecturer of the Arabic education department at Islamic State University of Sunan Ampel Surabaya. The collected data is processed and analyzed with data reduction, data display, and conclusion drawing. After that, the results are narrated. The results showed that all stages of CLM implementation, except the discussion stage, were well done, i.e. reflection, recorded conversations, transcriptions, language analysis, and free conversation. The discussion stage was still not running optimally because of some factors including the lack of vocabulary in speaking and the technical obstacles during the recording process.